Hubungan Dukungan dan Koping Keluarga Dengan Tingkat Kekambuhan Pada Pasien Skizofrenia di Wilayah Kerja Puskesmas Lubuk Buaya Padang tahun 2025 - Riza Anatul Fausia; Edo Gusdiansyah; Amelia Susanti (CV. ITTC INDONESIA, 2026)
The prevalence of schizophrenia affects approximately 24 million people, or 1 in 300 (0.32%) worldwide. The number of schizophrenia patients in Indonesia increased from 1.7% in 2013 to 7% in 2018. In 2023, West Sumatera ranked eighth in Indonesia with 39.1% of the population suffering from mental disorde. The purpose of this study was to determine the relationship between family support and coping with relapse rates in schizophrenia patients in the Lubuk Buaya Padang Community Health Center working area in 2025. This was an analytical study with a cross-sectional design. The study was conducted from March to August 2025. Data collection was conducted over a 10-day period, from June 11 to 21, 2025. The population of all families with schizophrenia in the Lubuk Buaya Padang Community Health Center working area was 234, with a sample size of 70 individuals. The sampling technique was proportional random sampling. The study used a questionnaire and interviews. Data were analyzed univariately and bivariately using the Chi-Square statistical test. The results showed that less than half (48.6%) of schizophrenia patients had a high relapse rate. Less than half (47.1%) had a supportive family. Less than half (48.6%) of respondents reported family coping skills in schizophrenia patients. There was a relationship between family support and coping with the relapse rate of schizophrenia patients in the Lubuk Buaya Padang Community Health Center (p-value = 0.000). The conclusion is that there is a relationship between family support and family coping and relapse in schizophrenia patients. It is hoped that psychiatric nurses can provide education through leaflets to families about proper home care for mental patients to prevent schizophrenia relapse in family caregivers..